2020
DOI: 10.1021/jacs.0c05505
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Self-Assembly of New Metastable Tin Vanadium Selenides Using Composition and Nanoarchitecture of Precursors

Abstract: In solid-state chemistry, the direct reaction of elements at low temperatures is limited by low solid-state interdiffusion rates. This and the limited number of processing parameters often prevent the synthesis of metastable compounds. Precisely controlling the number of atoms and nanoarchitecture of layered elemental precursors enabled the selective synthesis of two closely related metastable tin vanadium selenides via near-diffusionless reactions at low temperatures. Although the nanoarchitectures of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The limited mobility of ions and atoms in solids limits the rate of solid-state reactions compared to solution- and gas-phase reactions , and contributes to typically long (multiday) reaction times. High temperatures are often used to enhance transport and accelerate reactions, but they can be a liability when targeting metastable phases. Higher reaction temperatures favor the thermodynamic product, while lower temperatures, along with shorter reaction times, may be needed to enable synthesis of metastable phases by avoiding their transformation to more stable products. In this endeavor, in situ studies during solid-state reactions can provide valuable feedback to guide synthesis, , including the temperature range at which different products or intermediates form . In typical in situ powder X-ray diffraction studies, mixtures of precursors, as crystalline powders, are heated and data are collected as a function of temperature to evaluate changes in structure and phase distribution. ,, Previous studies of this type have revealed extreme complexity in solid-state reaction landscapes; several different metastable polymorphs can be observed during a single reaction. , …”
mentioning
confidence: 99%
“…The limited mobility of ions and atoms in solids limits the rate of solid-state reactions compared to solution- and gas-phase reactions , and contributes to typically long (multiday) reaction times. High temperatures are often used to enhance transport and accelerate reactions, but they can be a liability when targeting metastable phases. Higher reaction temperatures favor the thermodynamic product, while lower temperatures, along with shorter reaction times, may be needed to enable synthesis of metastable phases by avoiding their transformation to more stable products. In this endeavor, in situ studies during solid-state reactions can provide valuable feedback to guide synthesis, , including the temperature range at which different products or intermediates form . In typical in situ powder X-ray diffraction studies, mixtures of precursors, as crystalline powders, are heated and data are collected as a function of temperature to evaluate changes in structure and phase distribution. ,, Previous studies of this type have revealed extreme complexity in solid-state reaction landscapes; several different metastable polymorphs can be observed during a single reaction. , …”
mentioning
confidence: 99%
“…The local composition is another important parameter, which is controlled by the relative layer thicknesses of each element deposited. 131,144 The activation barrier for nucleating a crystalline compound depends on the local composition. For homogenous amorphous alloys, the lowest nucleation energy is observed for amorphous intermediate compositions that corresponded to the stoichiometry of the compound.…”
Section: Modulated Elemental Reactants (Mer)mentioning
confidence: 99%
“…43,155–158 Other heterostructures incorporating novel constituents and combinations of constituents that do not exist on equilibrium phase diagrams have also been reported, based on intergrowths of different layered compounds (including Bi 2 Te 3 , TiTe 2 , TiSe 2 , MoSe 2 , VSe 2 ,) and structural fragments of compounds with 3D structures, (including PbSe, SnSe, BiSe, LaSe, and GeSe 2 ). 41,144,154,155,159–162 Key to the formation of a specific heterostructure is controlling the deposition parameters so that the precursors contain the desired ratio of metal atoms to chalcogen atoms (2 : 3, 1 : 2, or 1 : 1) for the Bi 2 Te 3 -type, CdI 2 -type structures and MX layers respectively) and the correct number of atoms to form an integer number of crystalline layers of the targeted constituents.…”
Section: Modulated Elemental Reactants (Mer)mentioning
confidence: 99%
“…Understanding the mechanisms behind chemical reactions is one of the biggest issues in materials chemistry, since this makes it possible to create compounds with the desired structures or to optimize reactions toward functional uses. However, reactions in solid‐state crystalline compounds are rather poorly understood [ 1 ] compared with molecular reactions whose steps have been analyzed with nuclear magnetic resonance (NMR) and other spectroscopies. This is partly because solid‐state reactions generally require high temperatures; thus, it is relatively difficult to monitor them by using in‐situ methods.…”
Section: Introductionmentioning
confidence: 99%